ANALISIS FUNGSI PENGADILAN TATA USAHA NEGARA DAN PERANANNYA DALAM MENGATUR HUBUNGAN ANTARA PEMERINTAH DAN MASYARAKAT DALAM PENGELOLAHAN LINGKUNGAN HIDUP - Shinta Novita Sari Silalahi; Yudi Kornelis; Diki Zukriadi (Cahaya Ilmu Bangsa, 2024)
The State Administrative Court (PTUN) is one of the important instruments in the Indonesian legal system aimed at overseeing government administrative actions and ensuring justice for the public. This research was conducted using qualitative methods with a descriptive analytical approach. The results indicate that PTUN plays a vital role in controlling government administrative actions and providing a legal protection mechanism for the public. PTUN functions as an independent overseer ensuring that government administrative decisions are made based on the prevailing laws and do not harm public interests. Through fair and transparent rulings, this research provides valuable insights for policymakers and legal practitioners to continuously improve and strengthen the function of PTUN within the Indonesian legal system